Kratom (Mitragyna speciosa) Leaf Ethanol Extract Showed In Vivo Analgesic Activity - Prasetya, Rahmad A.; Sudarwati, Tri P.L (Pharmacology and Clinical Pharmacy Research, 2023)
Analgesic drugs like morphine and other opioids exhibit several harmful effects. Thus, the exploration of a new and safer analgesic drug is necessary. Utilizing Indonesia's biodiversity richness, medicinal plants can serve as an alternative source of novel analgesic drugs. Here, we show the analgesic activity of Kratom (Mitragyna speciosa) leaf ethanol extract (KE) in formaldehyde-induced rat (Rattus norvegicus) models. The effect of KE was examined by observing the duration of spontaneous nociceptive behavior such as paw licking or limp leg. The result showed that rats treated with 70 mg/kg KE demonstrated significantly (p<0.01) decreased nociceptive behavior compared to those receiving vehicles. However, a higher KE dose (210 mg/kg) failed to increase the analgesic effect and showed a slight reduction (not significant) compared to the control group. These findings proved that kratom leaf ethanol extract has the potential to alleviate painful conditions.